2012
DOI: 10.1115/1.4006584
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ribs and Tip Wall Distance on Heat Transfer for a Varying Aspect Ratio Two-Pass Ribbed Internal Cooling Channel

Abstract: Internal cooling channels with differing aspect ratios are typically found in gas turbine blades due to the varying thickness of the blade from the leading to trailing edge. These serpentine passages often contain several 180 deg bends, which are sharp edged in the region of the blade tip. The 180 deg bend has a pronounced effect on the heat transfer characteristics in the outlet channel and tip wall, where a strong influence is seen due to the divider wall-to-tip wall distance in the bend. The present study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…It is shown that the overall heat convection strength reaches the highest when the width is 0.88 times the height. A similar conclusion is reached by Jenkins et al (2013) that the small width enhances the downstream heat convection strength in the second pass. Erelli, Saha, and Panigrahi (2015) research the influence of different bend shapes on the forced convection performance and flow energy loss in a two-pass passage.…”
Section: Introductionsupporting
confidence: 76%
“…It is shown that the overall heat convection strength reaches the highest when the width is 0.88 times the height. A similar conclusion is reached by Jenkins et al (2013) that the small width enhances the downstream heat convection strength in the second pass. Erelli, Saha, and Panigrahi (2015) research the influence of different bend shapes on the forced convection performance and flow energy loss in a two-pass passage.…”
Section: Introductionsupporting
confidence: 76%
“…It is shown that, for the non-rotating cases, the sensitivity of the overall heat transfer performance to changes in the heating conditions is very low. Numerical simulations match well with our own experiments and the data obtained by Jenkins et al [154]. Tanda [136] reports a heat transfer rate around 8% lower than our own results, but it is within a reasonable range since the aspect ratios of both tests are different.…”
Section: Evolution Of Overall Heat Transfer Performancesupporting
confidence: 89%
“…The 90 ribs have higher thermal performance than those of 60 and 45 angled ribs. [26] Smooth outer wall 30 1.8 Jenkins et al [13] Smooth outer wall 100 1.59 Bunker [29] Smooth outer wall 200 1.37 Xie et al [32] Smooth outer wall 200 1.20 Han et al [26] Smooth outer wall, but ribbed inlet and outlet 30 2.5e2.7 Jenkins et al [13] Smooth outer wall, but ribbed inlet and outlet 100 2.27 Present study…”
Section: Thermal Performancementioning
confidence: 87%
“…When the inlet/outlet channels were turbulated, larger heat transfer augmentation factors (2.5-2.7 and 2.27) in the turn region were found by Han et al [26] and Jenkins et al [13], respectively. The present study indicates that the ribs on the outer wall improve the average Nusselt number ratio from 1.97 to 2.69-2.92 at Re ¼ 20,000.…”
Section: Average and Non-uniformity Of Heat Transfermentioning
confidence: 89%
See 1 more Smart Citation